Perbaikan Waktu Set Up Produksi Hot Stamping Foil Menggunakan Metode Single Minute Exchange Of Dies - Sofyan Assauri; Gunawan Mohammad; Dwi Retna Sulistyawati; Muhammad Choiru Zulfa; Gun Sudiryanto (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2025)
All companies hope for an effective and efficient production system, but an imperfect production system means that PT XYZ must improve its production activities. The company strives to produce good products followed by a high level of productivity. In this research, we investigate a case at PT XYZ which produces hot stamping foil in the rewind section. This research found that there was waste that occurred in set-up replacement activities in production. Because it requires a long processing time, we perfected the system by implementing the Single Minute Exchange of Dies (SMED) method, then the process optimized internal activities in the set-up process. The application of the SMED concept is carried out by changing internal activities into external activities with the addition of helpers. This research aims to provide a more effective and efficient set-up replacement process so that machine downtime can be reduced. The results of this research show a 52% reduction in set-up time obtained by adding a helper with a time before implementation of 58 minutes to 30 minutes. This research concludes that SMED is effective in reducing machine set-up time and increasing the efficiency of the production process with benefits after implementing the SMED method by adding a helper of Rp. 10,649,336. In this way, implementing the SMED method helps companies increase production set-up replacement times in the rewind section.